Milling and Public Warnings. Issue 5 (June 2018) - Wood, Michele M.; Mileti, Dennis S.; Bean, Hamilton; Liu, Brooke F.; Sutton, Jeannette; Madden, Stephanie
Given the potential of modern warning technology to save lives, discovering whether it is possible to craft mobile alerts for imminent events in a way that reduces people's tendency to seek and confirm information before initiating protective action is essential. The purpose of this study was to examine the possibility of designing messages for mobile devices, such as Wireless Emergency Alert (WEA) messages, to minimize action delay. The impact of messages with varied amounts of information on respondents' understanding, believing, personalizing, deciding, and intended milling was used to test Emergent Norm Theory, using quantitative and qualitative methods. Relative to shorter messages, longer public warning messages reduced people's inclination to search for and confirm information, thereby shortening warning response delay. The Emergent Norm Theory used herein is broader in application than the context-specific models provided by leading warning scholars to date and yields deeper understanding about how people respond to warnings.